Sequential treatment of afatinib and osimertinib or other regimens in patients with advanced non‐small‐cell lung cancer harboring EGFR mutations: Results from a real‐world study in South Korea. (13th July 2021) - Kim, Taeyun; Jang, Tae Won; Choi, Chang Min; Kim, Mi‐Hyun; Lee, Sung Yong; Park, Cheol‐Kyu; Chang, Yoon Soo; Lee, Kye Young; Kim, Seung Joon; Yang, Sei Hoon; Ryu, Jeong Seon; Lee, Jeong Eun; et al.
Abstract: Objectives: The optimal sequence for the administration of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) for treating non‐small cell lung cancer (NSCLC) is still unclear. This study aimed to evaluate the efficacy of sequential afatinib and osimertinib treatment in patients with NSCLC harboring EGFR mutations. Materials and methods: Electronic records of patients with EGFR‐mutated NSCLC, who were administered afatinib and osimertinib (group A) or other chemotherapy (group B) between October 2014 and 2019, across 16 hospitals in South Korea were reviewed. The primary outcome, time on treatment (TOT), secondary outcome, and overall survival (OS) were estimated using the Kaplan–Meier method and log‐rank test. Multivariate analyses were performed using the Cox proportional hazards model. Results: Of the 737 patients who received frontline afatinib treatment, 324 with complete records were selected (group A: 126, group B: 198). All patients in group A were T790M positive after afatinib, while patients in group B were all negative or unknown. The median TOT was 35.4 months (95% confidence interval [CI]: 27.7−45.6) in group A and 20.8 months (95% CI: 19.4−24.0) in group B. The median TOT with afatinib was 13.0 months (95% CI: 12.0−13.9) overall and 15.7 months (95% CI: 13.9−17.3) in group A. The 2‐ and 3‐year survival rates were 86.0 and 69.3% in group A and 75.9 and 55.3% in group B, respectively. Conclusion: Sequential afatinib and osimertinib treatment resulted in better survival rates than treatment with afatinib followed by other chemotherapies. Abstract : Our study evaluated the real‐world efficacy of sequential treatment of afatinib and osimertinib, and compared it with other chemotherapies as a second‐line treatment. Promising real‐world data on first‐line afatinib and second‐line osimertinib may maximize sustained clinical benefit with avoiding chemotherapy and may warrant consideration, though tailored personalized approaches are necessary.